2007
DOI: 10.3233/jad-2007-11105
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Pin1 in the Development of Alzheimer's Disease

Abstract: Pin1 protein, a peptidyl-prolyl cis-trans isomerase plays an important regulatory role in neuronal function. Recent studies indicate that Pin1 may promote the dephosphorylation of tau and restore its ability to bind to and polymerize microtubles. Previous studies on postmortem human brains showed that Pin1 is down-regulated in advanced Alzheimer's disease (AD) brains compared to age-matched non-demented controls. Because AD is a slowly progressive disease with a preclinical period that can last years, the abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Following death, all available clinical data were reviewed by an expert neurologist blinded to neuropathology and a clinical diagnosis was rendered. MTG and MFG samples were examined from 29 NI, 28 MCI, and 23 AD cases as previously diagnosed [8]. Caudate and cerebellar samples were examined from 12 NI, 10 MCI, and 11 AD cases.…”
Section: Methodsmentioning
confidence: 99%
“…Following death, all available clinical data were reviewed by an expert neurologist blinded to neuropathology and a clinical diagnosis was rendered. MTG and MFG samples were examined from 29 NI, 28 MCI, and 23 AD cases as previously diagnosed [8]. Caudate and cerebellar samples were examined from 12 NI, 10 MCI, and 11 AD cases.…”
Section: Methodsmentioning
confidence: 99%
“…The immunoprecipitated proteins were eluted by adding ImmunoPure® Elution Buffer and then analyzed by Western blotting with anti-HNE and anti-NEP polyclonal antibodies. The density of the NEP and HNE blotting bands were quantified by ImageJ software (1.37v, Wayne Rasband, National Institutes of Health,) as described [56, 57]. The ratio of HNE/NEP was calculated from the same sample to assess the relative level of HNE-NEP adducts.…”
Section: Methodsmentioning
confidence: 99%
“…First, Wang et al [21] suggested that reduced Pin1 activity in the frontal cortex of patients with mild cognitive impairment contributes to the initial accumulation of hyperphosphorylated tau and is then followed, in a more advanced stage of the disease, by a compensatory upregulation of the Pin1 gene that counteracts A ␤ plaque formation. Consistently with this hypothesis, in PBMCs of subjects with overt disease, we observed a significant increase in Pin1 gene expression together with a significant decrease in gene promoter methylation.…”
Section: Discussionmentioning
confidence: 99%